Volcanic and Seismic Source Modeling: An Open Tool for Geodetic Data Modeling - Trasatti, Elisa (Frontiers in Earth Science, 2022)
Volcanic and Seismic source Modelling (VSM) is an open source Python tool to model ground deformation. VSM allows the user to choose one or more deformation sources of various shapes as forward model among sphere, spheroid, ellipsoid, rectangular dislocation, and sill. It supports multiple datasets from most satellite and terrestrial geodetic techniques: Interferometric SAR, GNSS, levelling, Electronic Distance Measurements, tiltmeters and strainmeters. Two sampling algorithms are available, one is a global optimization algorithm based on the Voronoi cells and yields the best-fitting solution, and the second follows a probabilistic approach to pa-rameters estimation based on the Bayes theorem and the Markov chain Monte Carlo method. VSM can be executed as Python script, in Jupyter Notebook environments or by its Graphical User Interface. Its broad applications range from high level research to teaching, from single stud-ies to near real-time hazard estimates. Potential users range from early career scientists to experts. It is freely available on GitHub (https://github.com/EliTras/VSM) and is accompanied by step-by-step documentation in Jupyter Notebooks. The paper presents the functionalities of VSM and test cases to describe its use and comparisons among possible settings.